Bite-Sized Democracy: The Virtues of Incremental Change - Mills, Peter (Maine Policy Review, 2010)
In the Margaret Chase Smith Essay, Peter Mills draws on his long years of public service in both houses of the Maine Legislature to reflect on the values of gradual, incremental change in public policy.